The efflux pumps Rv1877 and Rv0191 play differential roles in the protection of Mycobacterium tuberculosis against chemical stress - Sao Emani, Carine; Reiling, Norbert (Frontiers in Microbiology, 2024)
Background: It was previously shown that GlnA3sc enabled Streptomyces coelicolor to survive in excess polyamines. However, subsequent studies revealed that Rv1878, the corresponding Mycobacterium tuberculosis (M.tb) ortholog, was not essential for the detoxification of spermine (Spm), in M.tb. On the other hand, the multi-drug efflux pump Rv1877 was previously shown to enable export of a wide range of compounds, while Rv0191 was shown to be more specific to chloramphenicol.Rationale: Therefore, we first wanted to determine if detoxification of Spm by efflux can be achieved by any efflux pump, or if that was dependent upon the function of the pump. Next, since Rv1878 was found not to be essential for the detoxification of Spm, we sought to follow-up on the investigation of the physiological role of Rv1878 along with Rv1877 and Rv0191.Approach: To evaluate the specificity of efflux pumps in the mycobacterial tolerance to Spm, we generated unmarked ∆rv1877 and ∆rv0191 M.tb mutants and evaluated their susceptibility to Spm. To follow up on the investigation of any other physiological roles they may have, we characterized them along with the ∆rv1878 M.tb mutant.The ∆rv1877 mutant was sensitive to Spm stress, while the ∆rv0191 mutant was not. On the other hand, the ∆rv1878 mutant grew better than the wild-type during iron starvation yet was sensitive to cell wall stress. The proteins Rv1877 and Rv1878 seemed to play physiological roles during hypoxia and acidic stress. Lastly, the ∆rv0191 mutant was the only mutant that was sensitive to oxidative stress.The multidrug MFS-type efflux pump Rv1877 is required for Spm detoxification, as opposed to Rv0191 which seems to play a more specific role. Moreover, Rv1878 seems to play a role in the regulation of iron homeostasis and the reconstitution of the cell wall of M.tb. On the 3 | P a g e other hand, the sensitivity of the ∆rv0191 mutant to oxidative stress, suggests that Rv0191 may be responsible for the transport of low molecular weight thiols.